MANAJEMEN OTONOMI PENDIDIKAN DI INDONESIA - Emmi Kholilah Harahap (Pascasarjana IAIN Metro, 2016)
Education decentralization means that the delegation of powers and wider authority to the regions in planning and making their own decisions in addressing the problems faced in the field of education.Education decentralization provides the authority to school as known as education autonomy. That authority gives the wider space to the school in managing natural and human resources based on the regional potential. Education autonomy does not stop at the local district / city level but to the level of the school as the spearhead of education.The transfer of authority at the school level can help the school in making expansion program direction based on the regional condition and potential.